2019
DOI: 10.1017/cjn.2018.352
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to Guidelines at a Stroke Prevention Clinic: A Follow-up Study

Abstract: BackgroundIn 2010, we published our stroke prevention clinic’s performance as compared to Canadian stroke prevention guidelines. We now compare our clinic’s adherence with guidelines to our previous results, following the implementation of an electronic documentation form.MethodsAll new patients referred to our clinic (McGill University Health Center) for recent transient ischemic attack (TIA) or ischemic stroke between 2014 and 2017 were included. We compared adherence to guidelines to our previous report (N=… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Similarly, Chen et al reported that in their multivariate logistic regression analysis a diagnosis of diabetes was independently associated with failing to meet BP targets. 12 When we examined DBP target attainment in patients with diabetes using the non-diabetes DBP target, there was no longer a significant difference between subjects with diabetes compared to those without. Thus, the greater proportion of people with diabetes not meeting the DBP target in this study is due, at least in part, to target levels that recommend tighter control.…”
Section: Diabetes Had the Strongest Association With Not Achieving Bp Targetsmentioning
confidence: 96%
See 3 more Smart Citations
“…Similarly, Chen et al reported that in their multivariate logistic regression analysis a diagnosis of diabetes was independently associated with failing to meet BP targets. 12 When we examined DBP target attainment in patients with diabetes using the non-diabetes DBP target, there was no longer a significant difference between subjects with diabetes compared to those without. Thus, the greater proportion of people with diabetes not meeting the DBP target in this study is due, at least in part, to target levels that recommend tighter control.…”
Section: Diabetes Had the Strongest Association With Not Achieving Bp Targetsmentioning
confidence: 96%
“…Our finding that 64.3% of patients met SBP and DBP targets is consistent with previously published Canadian studies that reported 46% to 83% of stroke patients meet target. [10][11][12] Two studies of patients attending an initial visit at a stroke prevention clinic described 83% and 76% BP target attainment, respectively. 10,12 A lower proportion of target attainment (46%) was reported in an outpatient study of patients with stroke or transient ischemic attack (TIA).…”
Section: A Gap Exists In Bp Target Attainment In Canadamentioning
confidence: 99%
See 2 more Smart Citations